PENGARUH KREATIVITAS DAN KECERDASAN SPIRITUAL TERHADAP EFIKASI DIRI DAN KEMANDIRIAN MAHASISWA JURUSAN MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS ISLAM MAJAPAHIT (UNIM) MOJOKERTO - Sundari, Sundari (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2015)
This study aims to analyze the influence of creativity and spiritual intelligence to the students self-efficacy. The object in this study were management students of the Economics faculty at UNIM management (Islamic University of Majapahit) Mojokerto 2013/2014. This study used Simple random sampling. The number of samples which were used in this study were 113 people. The data collection techniques used were questionnaires, interviews, and documentation. The method of analysis was Structural Equation Modeling (SEM). The results showed that creativity gives significant effect on students self-efficacy. Creativity influences independence. Spiritual intelligence influences students self-efficacy. Self-efficacy influences student independence. However, Spiritual intelligence does not affect the independence of the student. Creativity does not affect the independence through student self-efficacy. Spiritual intelligence does not affect the independence through self-efficacy